Clinical neurology and neurosurgery (Assen, the Netherlands : Van Gorcum, 1974)
"Clinical neurology and neurosurgery is devoted to publishing papers and reports on the clinical aspects of neurology and neurosurgery. It is an international forum for papers of high scientific standard that are of interest to neurologists and neurosurgeons world-wide."
Published: Elsevier Science Publishers B.V., 1992-
Some nos. issued in combined form.
Has supplements.
Description based on: Vol. 77, issue 2 (Dec. 1974); title from contents screen (ScienceDirect, viewed Nov. 14, 2005).
Latest issue consulted: Vol. 107, issue 6 (Oct. 2005), viewed Nov. 14, 2005.
Keywords: Neurology -- Periodicals; Nervous system -- Surgery -- Periodicals; Neurologie -- Périodiques.; Neurochirurgie -- Périodiques.; Nervous system -- Surgery; Neurology; Neurology -- Periodicals; Neurosurgery -- Periodicals; Neurology; Neurosurgery; Neurology -- periodicals; Neurosurgery -- periodicals; Electronic journals